Legal Protection of Copyright for Traditional Cultural Expressions of Traditional Ceremonies in West Java - Defna Nobirianto Putra; Reh Bungana Beru Perangin-angin; Angel Angelina Putri (Department of Civic Education, 2023)
Indonesia is a vast country with a population exceeding 200 million and cultural diversity that emerges from Sabang to Merauke. This cultural diversity has aspects of Intellectual Property Rights (IPR), which give rise to various kinds of intellectual creations within the scope of art, literature and science. The results of these intellectual creations are generally referred to as traditional knowledge. Traditional knowledge is knowledge possessed by a community for generations, which includes the management of biological wealth, such as songs, stories, legends, as well as arts and culture of other communities. The use of the term traditional knowledge is applied to all terms that are still included in traditional intellectual works, both in the fields of art, literature and science as well as intellectual works in the industrial sector. In relation to this broad traditional knowledge, there is another term known as cultural tradition (folklore). it became an expression of traditional culture. One form of traditional cultural expression found in West Java is the traditional ceremony. Traditional ceremonies in each region have different characteristics in Indonesia. As one of the expressions of traditional culture, traditional ceremonies are a form of intellectual work that grows and develops from and within a communal society, which is then passed down from generation to generation in its preservation. Traditional ceremonies in the West Java region are a form of cultural heritage that must be given legal protection in the form of Intellectual Property Rights (IPR) to protect the nation's cultural heritage.